Production and Risk Leveling in the Intertemporal Capital Asset Pricing Model - Grinols, Earl L. (Journal of Finance, 1984)
This paper extends Merton's intertemporal capital asset pricing model with multiple consumers to include a description of the supply of traded securities. The production decisions of firms are described in a model with stochastic investment opportunities and incomplete markets. Firms maximize the welfare of their stockholders based on the sum of dollar values placed on the projects by shareholders of the firm. The monetary value to stockholders of a marginal change in the contract structure due to changing firm production is analyzed. In this setting, the competitive market achieves an appropriately defined Nash-Constrained Pareto Optimum. Sufficient conditions for investor unanimity, market-value maximization by firms, and the equilibrium to achieve a Constrained Pareto Optimum and full Pareto Optimum are derived.